Fatigue Risk Management in the Logistics and Aviation Sectors: A Multi-Criteria Approach - ERDEN, Cemile; İLBAŞ, Ahmet; KAYA, Hakan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
Employees working in the logistics and aviation sectors are heavily exposed to fatigue risks due to challenging factors such as long working hours, irregular shift systems, high workload, and intense stress. Given the high-reliability nature of these industries, fatigue is not merely a health issue but a critical threat to operational safety and service quality. In this study, a hybrid Multi-Criteria Decision-Making (MCDM) approach was adopted to identify and analyze the main factors causing fatigue risk. The causal relationships among these factors were analyzed using the Decision Making Trial and Evaluation Laboratory (DEMATEL) method, while their relative significance levels were evaluated with the Best-Worst Method (BWM). Eight criteria were determined based on a comprehensive literature review and expert opinions, followed by a decision-making process involving 20 industry experts. According to the DEMATEL results, "K4-Task continuity," "K6-Physiological conditions," and "K7-Level of training and awareness" emerged as the primary causal factors, indicating that improvements in these areas trigger positive effects on other variables. Meanwhile, "K1-Workload intensity" and "K2-Shift schedule and working hours" were identified as result factors. Furthermore, the BWM results highlighted that "K5-Psychological stress level," "K2-Shift schedule and working hours," and "K1-Workload intensity" were the criteria with the highest weights. Consequently, this study provides a robust framework for practitioners to prioritize fatigue risk management strategies, thereby enhancing both employee well-being and operational safety.